Penerapan Kesetaraan Gender dalam Lingkungan Sekolah - Azkia Ishaq; Nur Khasanah (Advances In Education Journal, 2025)
This article examines the implementation of gender equality in the school environment through curriculum integration and inclusive educational practices. Gender equality in education is crucial for creating a fair and discrimination-free learning space. The study highlights that a gender-responsive curriculum, which presents balanced representations of male and female roles across various subjects, effectively reduces gender stereotypes and discrimination. Furthermore, the active role of educators and support from school policies are essential in creating an inclusive educational environment. The research concludes that consistent implementation of gender perspective integration not only empowers students equally but also contributes significantly to achieving the Sustainable Development Goals (SDGs), particularly the goal of gender equality in education.